Ordinance No. 2284, § 1, TACOMA REVISED CHARTER AND ORDINANCES 800, 800-03 (1905 Allen & Lamborn). - (:unkn) unknown (My University, 1905)
All persons (except police officers and other persons whose duty it is to execute process or warrants or make arrests) who shall carry upon their persons any concealed weapons, consisting of a revolver, pistol or other firearms (except by written permit from the Chief of Police) or any knife (other than an ordinary pocket knife) or any dirk or dagger, sling shot or metal knuckles or any instrument by the use of which injury can be inflicted upon the person or property of any other persons. All persons (except peace officers as aforesaid) who shall draw, exhibit or attempt to use any deadly weapon upon, to or against another person within said City with intent to do bodily injury to such person.All persons (except peace officers as aforesaid and persons practicing at target shooting in a shooting gallery, duly licensed) who shall within the City limits fire off or discharge any gun or pistol or firearm of any kind, or bomb?"
Keywords: BRANDISHING; CARRY - CONCEALED; DISCHARGE